A three‐crystal spectrometer for high‐energy resolution fluorescence‐detected X‐ray absorption spectroscopy and X‐ray emission spectroscopy at SSRF. (18th October 2016) - Duan, Peiquan; Gu, Songqi; Cao, Hanjie; Li, Jiong; Huang, Yuying
Abstract : A Johann‐type spectrometer for the study of high‐energy resolution fluorescence‐detected X‐ray absorption spectroscopy, X‐ray emission spectroscopy and resonant inelastic X‐ray scattering has been developed at BL14W1 X‐ray absorption fine structure spectroscopy beamline of Shanghai Synchrotron Radiation Facility. The spectrometer consists of three crystal analyzers mounted on a vertical motion stage. The instrument is scanned vertically and covers the Bragg angle range of 71.5–88°. The energy resolution of the spectrometer ranges from sub‐eV to a few eV. The spectrometer has a solid angle of about 1.87 × 0 −3 of 4π sr, and the overall photons acquired by the detector could be 10 5 counts per second for the standard sample. The performances of the spectrometer are illustrated by the three experiments that are difficult to perform with the conventional absorption or emission spectroscopy. Copyright © 2016 John Wiley & Sons, Ltd.